Terpyridine Diphosphine Ruthenium Complexes as Efficient Photocatalysts for the Transfer Hydrogenation of Carbonyl Compounds. Issue 65 (27th September 2022) - Ballico, Maurizio; Alessi, Dario; Jandl, Christian; Lovison, Denise; Baratta, Walter
Abstract: The cationic achiral and chiral terpyridine diphosphine ruthenium complexes [RuCl(PP)(tpy)]Cl (PP=dppp (1 ), ( R, R )‐Skewphos (2 ) and ( S, S )‐Skewphos (3 )) are easily obtained in 85–88 % yield through a one‐pot synthesis from [RuCl2 (PPh3 )3 ], the diphosphine and 2, 2′:6′, 2′′‐terpyridine (tpy) in 1‐butanol. Treatment of 1 –3 with NaPF6 in methanol at RT affords quantitatively the corresponding derivatives [RuCl(PP)(tpy)]PF6 (PP=dppp (1 a ), ( R, R )‐Skewphos (2 a ) and ( S, S )‐Skewphos (3 a )). Reaction of [RuCl2 (PPh3 )3 ] with ( S, R )‐Josiphos or ( R )‐BINAP in toluene, followed by treatment with tpy in 1‐butanol and finally with NaPF6 in MeOH gives [RuCl(PP)(tpy)]PF6 (PP=( S, R )‐Josiphos (4 a ), ( R )‐BINAP (5 a )) isolated in 78 % and 86 % yield, respectively. The chiral derivatives have been isolated as single stereoisomers and 3 a, 4 a have been characterized by single crystal X‐ray diffraction studies. The tpy complexes with NaO i Pr display high photocatalytic activity in the transfer hydrogenation (TH) of carbonyl compounds using 2‐propanol as the only hydrogen donor and visible light at 30 °C, at remarkably high S/C (up to 5000) and TOF values up to 264 h −1 . The chiral enantiomers 2, 2 a and 3, 3 a induce the asymmetric photocatalytic TH of acetophenone, affording ( S )‐ and ( R )‐1‐phenylethanol with 51 and 52 % ee, respectively, in a MeOH/2‐propanol mixture. Abstract : The new cationic ruthenium [RuCl(PP)(tpy)]X (X=Cl, PF6 ) complexes, prepared from [RuCl2 (PPh3 )3 ] a diphosphine and 2, 2′:6′, 2′′‐terpyridine (tpy), promote the photocatalytical transfer hydrogenation (TH) of carbonyl compounds in 2‐propanol under mild conditions. Unprecedented asymmetric catalytic TH of acetophenone driven by light was obtained with ruthenium tpy complexes containing the chiral Skewphos diphosphine.